The Wilsonian Toolbox: The Wilsonian Arguments of the Korean Independence Movement - Plambeck-Grotum, Cecilie (Culture and History: Student Research Papers, 2023)
Following the founding of the League of Nations and as the wave of idealism that came to be known as the Wilsonian Moment swept the planet, the Korean independence movement gathered to appeal against Japanese colonial rule. This article sets out to uncover how the idealism of Wilsonialism and the establishment of the League of Nations provided independence movements such as the Korean with a toolbox of arguments along with a platform on which to be heard. It also analyses how these arguments changed from the Koreans’ initial appeal in 1919 to an attempt made in 1932 following a period of increasing conflict surrounding Japan through the 1920s and early 30s. This article demonstrates how the inspirational effect of the Wilsonian Moment and the League of Nations had profound effects on marginalized movements such as the Korean and their ability to argue their case in the world in the face of political turmoil, international crises, and global power struggles.